Using accelerometry to classify physical activity intensity in older adults: What is the optimal wear-site?. Issue 8 (13th September 2020) - Duncan, Michael J.; Rowlands, Alex; Lawson, Chelsey; Leddington Wright, Sheila; Hill, Matt; Morris, Martyn; Eyre, Emma; Tallis, Jason
Abstract : This study aimed to determine the optimal accelerometer wear-site specific cut-points for discrimination of the sedentary time, light physical activity and moderate-to-vigorous physical activity (MVPA) in older adults. Twenty-three adults (14 females) aged 55–77 years wore a GENEActiv accelerometer on their non-dominant wrist, dominant wrist, waist and dominant ankle whilst undertaking eight, five-minute bouts of activity: lay supine, seated reading, slow walking, medium walking, fast walking, folding laundry, sweeping and stationary cycling. VO2 was assessed concurrently using indirect calorimetry. Receiver-operating-characteristic (ROC) analyses were used to derive wear-site specific cut-points for classifying intensity. Indirect calorimetry indicated that being lay supine and seated reading were classified as sedentary (<1.5 METs), laundry as light (1.51–2.99 METs) and sweeping, slow, medium and fast walking and cycling all classified as moderate intensity (>3 METs). Areas under ROC curves indicated that the classification of sedentary activity was good for the non-dominant wrist and excellent for all other wear sites. Classification of MVPA was excellent for the waist and ankle, good for the waist and poor for the dominant and non-dominant wrists. Overall, the ankle location performed better than in other locations. Ankle-worn accelerometry appears to provide the most suitable wear-site to discriminate between sedentary time and MVPA in older adults.